(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines theoretical interpretations of the concept of discourse within linguistic, pragmatic, and semiotic approaches. The relationship of discourse with text, speech, communicative situations, and extralinguistic factors is analyzed through the perspectives of various linguists. The study also explores the role of discourse in the anthropocentric paradigm, pragmalinguistics, and cognitive linguistics, highlighting its national-cultural and social characteristics. Furthermore, attention is given to the significance of discourse in communicative activity and to current issues in discourse analysis within contemporary linguistics.